Sensibilidade de Hymenaea stigonocarpa Mart. às condições ambientais do cerrado : análise de dinâmica de uso de água e do déficit hídrico do caule - Banga, Nelson Mário (2020)
The assessment of how environmental conditions affect tree water use is essential to understand the limits of its ability to survive under stress conditions. Hymenaea stigonocarpa Mart. ex Hayne (jatoba) is a dominant tree species in the Brazilian cerrado, which grows stressful environmental conditions such as low water availability in the soil, high atmospheric evaporative demand and the inability of the jatoba to access the deeper layers of the soil. To clarify how the environmental conditions of the cerrado affecting the daily use of water in the jatoba, sap flow velocity in the stem (V) and stem diameter variation (VDC) were monitored using thermal dissipation probes and dendrometer, respectively. Continuous variations in stem diameter were partitioned in order to estimate water deficit in the stem (TWD), as tree water status indicator. Also, meteorological variables and soil water content were measured during 2018 and 2019. The response of Fs and TWD to environmental variations was assessed using several regression models. The environmental conditions of the cerrado are causing restrictions on the daily use of water in the jatobá; these restrictions were observed under conditions of vapor pressure deficit (VPD) above 1.5 kPa and global solar radiation (Rg) above 10 MJ m-2 d -1 . There is no interspecific variability in response to environmental variations among the trees. The sap flow was reduced by almost 50% during the dry season, which suggests greater sensitivity to soil drought. This study provides support for understanding the dynamics of daily water use in trees exposed to frequent soil drought and dry atmosphere.